CIVIL LAW CHARACTERISATION OF THE INVESTMENT ADVICE AND PORTFOLIO MANAGEMENT - Didžiulis, Laurynas (Teisė, 2017)
The aim of this article is to analyse the legal nature of classical investment services provided by the investment advisors – investment advice and portfolio management, and to characterise these services in the light of Lithuanian private law.